Study of the relevance of visualisation of the clothing design process using the newest digital technologies - Навольська, Л. В.; Колосніченко, О. В.; Струмінська , Т. В.; Луцкер , Т. В.; Ременєва , Т. В. (Fashion Industry, 2025)
Purpose. To investigate the role and significance of digital technologies in visualizing the clothing design process. The study aims to conduct a comprehensive analysis of the impact of 3D modeling, augmented and virtual reality, and artificial intelligence on design procedures in the fashion industry. Methodology. The study is based on the use of information and analytical analysis of scientific sources for 2023 and 2025 on the digitalisation of the fashion industry; comparative analysis of traditional and digital visualisation methods; case analysis of innovative digital technologies in the fashion industry; empirical study of the functionality of software for visualising the clothing design process. Results. The relevance of visualizing the clothing design process is substantiated. A comparative analysis highlights the differences in efficiency between traditional and digitally enhanced design methods. The study identifies the key advantages of digital visualization in optimizing production processes. The integration of 3D modeling, augmented and virtual reality, and artificial intelligence significantly improves the effectiveness, quality, and competitiveness of garment production. Scientific novelty. The article comprehensively analyses the impact of digital technologies on the clothing design process in the context of global and local challenges for the first time. The scientific novelty of the study lies in identifying the main trends and prospects for implementing 3D modelling, augmented and virtual reality, and artificial intelligence technologies in the processes of the fashion industry. Practical value. The study’s results can be used to optimise clothing design processes and reduce costs for creating prototypes, especially in Ukrainian brands. The practical significance lies in the formulation of recommendations for specialists in the fashion industry regarding the optimal combination of digital visualisation innovations with traditional clothing design methods.